The Teaching Principal: An Untenable Position or a Promising Model? - Newton, Paul M.; Wallin, Dawn (Alberta Journal of Educational Research, 2013)
This paper reports on an interpretive study that examined the role of the teaching principal, particularly as it relates to principals’ moral and legal requirement to work as instructional leaders for student learning. A teaching principal is defined as a principal who has a “double load” or dual roles in teaching and administration (Clarke & Stevens, 2009). In this study, we explored the constitution and effects of this role on individuals and leadership practices of 12 rural teaching principals in Alberta and Manitoba. Findings reflect the need to develop policies that sustain the smaller schools which depend upon administrators capable of thriving in this dual role. Additionally, the way in which teaching principals practice as instructional leaders promises to enrich the literature on instructional leadership. Specifically, the practices that emerge through the teaching principalship are a unique adaptation of existing conceptualizations that offer considerable advantages over those that presuppose a full-time administrative appointment. Cet article rend compte d’une étude interprétative portant sur le rôle du directeur enseignant, notamment par rapport à l’exigence morale et juridique qu’ont les directeurs de travailler comme leaders pédagogiques. Un directeur enseignant en est un qui a une « double charge », qui joue deux rôles, un en enseignement et un en administration (Clarke & Stevens, 2009). Dans cette étude, nous avons exploré la création et les effets de ce rôle sur les individus et sur les pratiques de leadership de douze directeurs enseignants en milieu rural en Alberta et au Manitoba. Les résultats reflètent la nécessité de développer des politiques qui appuient les plus petites écoles qui dépendent d’administrateurs en mesure de prospérer dans le contexte de ce double rôle. De plus, les pratiques qu’emploient les directeurs enseignants dans leur capacité de leaders pédagogiques promettent d’enrichir la littérature sur le leadership pédagogique. Plus spécifiquement, les pratiques qui ressortent des pratiques des directeurs enseignants constituent une adaptation unique des conceptualisations existantes, une qui offre un nombre considérable d’avantages par rapport à celles qui présupposent un poste administratif à temps plein.